Impact of neighborhood and individual socioeconomic status on survival after breast cancer varies by race/ethnicity: The Neighborhood and Breast Cancer Study - Shariff-Marco, Salma (2014)
BACKGROUND: Research is limited on the independent and joint effects of individual- and neighborhood-level socioeconomic status (SES) on breast cancer survival across different racial/ethnic groups. METHODS: We studied individual-level SES, measured by self-reported education, and a composite neighborhood SES (nSES) measure in females (1,068 non-Hispanic whites, 1,670 Hispanics, 993 African-Americans, and 674 Asian-Americans), aged 18–79 years and diagnosed 1995–2008, in the San Francisco Bay Area. We evaluated all-cause and breast cancer-specific survival using stage-stratified Cox proportional hazards models with cluster adjustment for census block groups. RESULTS: In models adjusting for education and nSES, lower nSES was associated with worse all-cause survival among African-Americans (p-trend=0.03), Hispanics (p-trend=0.01) and Asian-Americans (p-trend=0.01). Education was not associated with all-cause survival. For breast cancer-specific survival, lower nSES was associated with poorer survival only among Asian-Americans (p-trend=0.01). When nSES and education were jointly considered, women with low education and low nSES had 1.4 to 2.7-times worse all-cause survival than women with high education and high nSES across all races/ethnicities. Among African-Americans and Asian-Americans, women with high education and low nSES had 1.6 to 1.9-times worse survival, respectively. For breast cancer-specific survival, joint associations were found only among Asian-Americans with worse survival for those with low nSES regardless of education. CONCLUSIONS: Both neighborhood and individual SES are associated with survival after breast cancer diagnosis, but these relationships vary by race/ethnicity. IMPACT: A better understanding of the relative contributions and interactions of SES with other factors will inform targeted interventions towards reducing long-standing disparities in breast cancer survival.